Directed drug delivery systems. Biotechnological aspects - Galkin, O.Yu.; Bondarenko, L.B.; Grishyna, A.S.; Dugan, O.M. (Біотехнологія, 2009)
Publications concerning methods of creation of the drug delivery systems based on liposomal forms and receptor-dependent endocytosis are summarized. The methods of use of the directed drug delivery systems in creation of anticancerogenical and antibacterial agents, vaccines and in gene therapy are examined.